(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
34 species of mosses found in the vicinity of the four companies of Nikolaev (Ukraine). They grow mostly in the wood stands of different age and composition as well as settle on anthroposubstrates. Most of the mosses live on the soil ecotopes (23 species). Specific features of the moss flora, in comparison with other local bryophyte flora of the steppe zone, is a fairly large number of multi-zone (cosmopolitan) bryophytes (29.4%) and small one of arid species (11.4%), almost the same number of monoecious and dioecious species, the dominant representatives of the factions synanthropic mosses (gemiapofitov, eventapofitov). The investigated mosses implement the life strategies of coenotical and ecotopic briopatients and pioneer brioexplerents.